New species of Pseudoscalibregma Ashworth, 1901 (Annelida: Scalibregmatidae Malmgren, 1867) from Brazil - Mendes, Samuel Lucas Da Silva Delgado; Paiva, Paulo Cesar De; Rizzo, Alexandra E. (Zootaxa, 2024)
Pseudoscalibregma Ashworth, 1901 is a small genus of the family Scalibregmatidae Malmgren, 1867. Currently, a total of eight valid species are accepted. Of these, the majority are found at great depths. This work contains the first report of Pseudoscalibregma to the Brazilian coast, with the description of three new species: Pseuscalibregma ermindae sp. nov., P. magalhaesi sp. nov. and P. parapari sp. nov. The material was sampled from the Brazilian southeast region, on Campos and Santos sedimentary basins, during scientific expeditions called “Santos Project—Santos Basin Environmental Characterization” and “Ambes Project—Espírito Santo Basin Assessment Project”, both coordinated by PETROBRAS/CENPES. We also include an identification key to Pseudoscalibregma species.